ANALISA MANAJEMEN DALAM PENYALURAN KREDIT PADA PT BANK BUKOPIN Tbk CABANG UTAMA SURABAYA - Nurhidayat, Mukhamad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is meant to find out the policy of credit provision at PT. Bank BUKOPIN Tbk, Main Branch Office Surabaya has implemented the 5C principles (Character, Collateral, Capital, Capacity, Condition of economic) and the prudential principle. On the other hand, this research is meant to find out the role of analysis which has been done by the Bank to the Bank customer which propose a credit is the analysis of financial aspect and non-financial. Qualitative method with case study is applied in this research at PT. Bank BUKOPIN Tbk which is a financial institution which fund is raised from the public in the form of savings and transfer back in the form of credit. The implementation of credit provision, congestion credit risk is a problem which severely affects the health of a bank, so bank is required to have a reliable management credit. Keywords: Credit analysis, Non Financial Analysis, and Financial analysis.